Study of Equipment Presses of Cocoa Powder (Theobroma cacao,L) to Produce Quality Fat Cocoa and Analysis of the Resulting - Chatib, Omil Charmyn; Sandra, Sandra; Asbani, Harly Meta (International Journal on Advanced Science, Engineering and Information Technology, 2015)
This study was conducted to determine the performance of the press tool brands CARVER type Model 3912 Hydraulic Unit in producing cocoa fat and then analyzing the product. This research was conducted at the Laboratory of Food and Agricultural Products Processing and Chemistry Laboratory, Agricultural Products Biochemistry Faculty of Agricultural Technology, University of Andalas, Padang in April-June 2014. In this study, conducted observations such as pressure, temperature, and time presses ideal in the process. While the manufacturing unit made a tool to improve the performance of the instrument and the acquisition of fat that is carried out according to treatment pressure of 8.05 MPa at a temperature of 130 oC, 150 oC and 170 oC for each repetition. After that, analyzing the free fatty acids, iodine number, saponification number, and the moisture content of the product is done. Based on studies conducted by the information obtained from the data base in the presses, pressure 8.05 MPa and a temperature of 130 oC obtained average - average yield of 51.57% fat for 3 repetitions. This explains that the tool operates properly. As for test analysis, free fatty acids, iodine number, saponification number, and moisture content for each sample at all treatment is not obtained in accordance with the quality standards of Fat Cocoa determined by ISO 3748:2009.